Studi Kasus Pengaruh Terapi Kombinasi Akupresur dan Kompres Hangat (Aku-SeHat) untuk Mengurangi Nyeri Sendi pada Lansia - Nur Oktafiani; Lita Heni Kusumawardani (UIMA Press, 2023)
Backgrounds: An elderly group is a high-risk group for suffering from health problems, one of which is joint pain. Joint pain in the elderly will affect their quality of life of the elderly. One of the complementary therapies to reduce joint pain in the elderly is a Combination Therapy of Acupressure and Warm Compresses (Aku-SeHat). Objectives: This case study aims to determine the effect of a Combination Therapy of Acupressure and Warm Compresses (Aku-SeHat) to reduce joint pain in the elderly. Methods: The research method uses a case study design. The sample used was 3 elderly with inclusion criteria belonging to having complaints of knee joint pain in the category of severe pain (scale 7-10) and being able to participate in therapy with predetermined procedures and time. Aku-SeHat therapy is carried out 7 times in 7 days for 30 minutes. Univariate data analysis is presented in the frequency distribution while bivariate analysis uses the Wilcoxon test. Results: The results of the case study showed that there was a significant effect of giving Aku-SeHat therapy to reduce joint pain in the elderly with the Wilcoxon test results obtained a p-value of 0.0001 (p <0.05). Conclusion: The results of the case study showed that there was a significant effect of giving Aku-SeHat therapy to reduce joint pain in the elderly. Therefore, it is hoped that Aku-SeHat therapy can be an alternative to complementary therapy as a nursing intervention to reduce joint pain.